Abundance of a cryptic generalist parasite reflects degradation of an ecosystem. Issue 10 (28th October 2020) - Artim, John M.; Nicholson, Matthew D.; Hendrick, Gina C.; Brandt, Marilyn; Smith, Tyler B.; Sikkel, Paul C.
Abstract: Ecosystem degradation due to anthropogenic activities is the primary issue of our times. Theoretical analyses as well as efforts to restore and manage ecosystems depend on comprehensive metrics of ecosystem function. In the case of complex ecosystems such as tropical coral reefs—especially where monitoring, management, and restoration are important—multiple metrics reflecting key functional groups are required to accurately reflect ecosystem function and when necessary, diagnose degree and kind of ecosystem degradation. We propose inclusion of the generalist ectoparasite functional group as a measure of ecosystem function of coral reefs. This functional group is adaptable to loss of other community members and may experience an increase in abundance as ecosystem function declines. Fish‐parasitic gnathiid isopods are a member of this group, resident though inconspicuous in coral‐reef communities. On Caribbean coral reefs, based on 938 light‐trap samples, we observed a negative correlation between abundance of smaller‐sized gnathiids and abundance of live coral, a natural predator of gnathiids. Plots grouped by coral cover—a measure of success of the ecosystem engineer—and ectoparasite abundance varied significantly in community composition including abundance of macroalgae, turf algae, and farming Stegastes spp. damselfish reflecting shifts in community structure. Changes in gnathiid abundance with respect to the abundance of organisms participating in each of the core functional processes driving coral‐reef ecosystems reflect broad connectivity of gnathiid parasites across the ecosystem. We conclude that the hyperabundance of a small, cryptic, generalist parasite, when used in combination with a metric of abundance of the primary ecosystem engineer, can provide one nuanced measure of the ecosystem vulnerability to collapse.